Black Eagle Child : the Facepaint narratives - Young Bear, Ray A. (Singular lives., 1992)
A candid, poetic account of childhood and young manhood through the eyes of a Native American, this vivid narrative is destined to become a central moral text for our time. Through the persona of Edgar Bearchild - a member of the Black Eagle Child Settlement - Ray A. Young Bear takes readers on an unforgettable "journey of words" as he documents grief and anguish countered by an abundance of humor, pride, and insight